Individual Insomnia Symptom and Increased Hazard Risk of Cardiocerebral Vascular Diseases: A Meta-Analysis - Hu, Shiyu; Lan, Tao; Wang, Yang; Ren, Lijie (Frontiers in Psychiatry, 2021)
Objective: Previous studies suggested that insomnia was associated with an increased risk of cardiocerebral vascular diseases (CVDs) but not clear in different insomnia symptoms. We performed a meta-analysis to investigate the association of individual insomnia symptoms and risk of CVDs. Methods: In this meta-analysis, we systematically searched published articles by using electronic databases including PubMed, Cochrane Library, MedLine, and Google Scholar. Studies were enrolled if they indicated clear insomnia symptoms, prospective, and evaluated the association of insomnia symptoms and CVD outcome in adults free of CVDs at baseline. Results: There were seven prospective cohort studies with sample sizes ranging from 2,960 to 487,200 included in this meta-analysis. Mean follow-up duration was 10.6 years. Insomnia symptoms of having difficulty initiating or maintaining sleep (DIS or DMS), non-restorative sleep (NRS), and early morning awakening (EMA) were analyzed in this study. All studies were compared under a random-effects model. NRS, DIS, and DMS were, respectively, related to 16% [hazard ratio (HR) 1.16, 95% CI 1.07–1.24], 22% (HR 1.22, 95% CI 1.06–1.40), and 14% (HR 1.14, 95% CI 1.02–1.27) higher risk of first-ever CVD incidence during the follow-up. Based on our analysis, EMA was not a risk factor of CVDs (HR 1.06, 95% CI 0.99–1.13). Conclusion: This study suggested that symptoms of DIS, DIM, or NRS were associated with a higher risk of CVD incidence in insomnia patients free of CVDs at baseline. But this association was not significant in insomnia patients complaining about EMA.